Estudio comparativo de un control predictivo y PID aplicado a un proceso didáctico de caudal. - Guambo Cain, Wilson Geovanny (2021)
The comparison between a Predictive control and a PID using a flow process, constitutes a favorable scenario for the analysis of control systems, to carry out such a comparison it is necessary to create the technical conditions for its implementation since none of the control elements used In this project (PLC S7-1200, NI myDAQ) it has libraries that allow its implementation on its physical memory, hence, an OPC communication platform was used, successfully establishing communication between the plant and the software that supports both real-time drivers. Once the conditions for its implementation have been created, each controller is designed in the Simulink software. From this stage, the process that requires the greatest effort is to find the appropriate tuning point that provides relative speed and stability to the system. Therefore, it is necessary to simulate the behavior of each of the controllers to later be implemented, making fine adjustments to their tuning values. The result of the implementation gives a very stable control in the flow management both for the PID control and for the Predictive control, settling its main differences in a much faster transient response for the PID control and with a better management of the variable in steady state by the Predictive control, but in general the performance for both controllers even in the rejection of disturbances is very even, this taking into account is evaluating and comparing their performance in the management of a system (SISO), which would incline the balance towards PID control because it is easier to implement, however this research objective is to constitute a basis for future work where performance in multivariable processes can be evaluated.